Lacan and religion - Dunlap, Aron (Durham Acumen, 2014)
Lacan and Religion presents students of religious studies and theology with a clear introduction to a famously complex thinker. Throughout, the theological analysis is set in the context of Lacan's ideas about psychoanalytical thought and practice. The book reveals Lacan to be one of the most incisive analysts of the "field of the divine." --from back cover.
Includes bibliographical references and index.
Keywords: Lacan, Jacques -- 1901-1981.; Psychoanalysis; Psychology and religion